Ionospheric F Layer Scintillation Weakening as Observed by COSMIC/FORMOSAT‐3 During the Major Sudden Stratospheric Warming in January 2013. Issue 9 (29th August 2020) - Yu, Tao; Ye, Hailun; Liu, Huixin; Xia, Chunliang; Zuo, Xiaomin; Yan, Xiangxiang; Yang, Na; Sun, Yangyi; Zhao, Biqiang
Abstract: Sudden stratospheric warming (SSW) events in Northern Hemisphere winter atmosphere play a significant effect on large ionospheric disturbances. Nevertheless, the SSW effects on small‐scale structure in ionosphere, that is, the ionospheric F layer irregularities, are generally lack of understanding. This work carefully studied the equatorial F layer scintillation during the SSW event extending from 4 January to 5 February in 2013 by using the data of COSMIC/FORMOSAT‐3 (a Constellation Observing System for Meteorology, Ionosphere, and Climate mission). The occurrence rate of ionospheric F layer scintillation was found to be apparently decreased by about 30% during the SSW period. This phenomenon was obviously seen in American sector (90°W–0°) and African sector (0°–90°E). Another prominent feature was the ~0.5 local time hour delay of maximum scintillation occurrence rate associated with the suppression of equatorial F layer irregularities in the first 2 hr after the sunset during the SSW event in January 2013. Key Points: It is the first time to study the response of small scale structure in ionosphere during SSW by COSMIC data sets The occurrence rate of ionospheric F‐layer scintillation weakened by about 30% during the January 2013 SSW event The weakening is obvious in American and African sectors, not obvious in other sectors, which are attributed to low scintillation in winter